Modelagem matemática e teoria da complexidade: diálogo multitemático no ensino superior - SANTOS, Neuma Texeira dos (Universidade Federal do Pará, 2022)
The research accomplished in this doctoral thesis was motivated by the interest in understanding whether the activities of Mathematical Modeling in College Education, discussed from the seven knowledge of Edgar Morin's complexity, allow the defragmentation of knowledge and the reconnection of knowledge, since the education of the 21st century needs a complex thinking, moved by the feeling of belonging to a planetary unity. In this way, the themes sought to monitor mangrove swamps, ducks (dendrocygna autumnalis) in different contexts, the Covid-19 pandemic, social networks, fake news, infographics and scientific dissemination, to articulate knowledge by developing face-to-face and on-line activities. The selection of empirical data was inspired by the methodological procedure of content analysis, and the discussion of data organized from the Modeling steps, proposed by Professor Rodney Bassanezi. The text was organized in the aggregation format, bringing together three connected and independent articles, accompanied by an integrating text, introduction and general considerations. The first article deals with a theoretical reflection on the epistemological foundations of Edgar Morin's theory of complexity, in order to identify the intertwining with Modeling, which enables the reconnection of knowledge. In the second article, an empirical activity was carried out, with the theme of setting in the mangrove. This field activity culminated in the multi-thematic approach of the third article. The research has shown that the Modeling approach, which provides complex thinking, is based on a transdisciplinary perspective. Facing the complexity of the problems experienced in this century, it is necessary to act beyond borders, allowing Mathematical Modeling to exist and enhance the articulation of knowledge, for the full exercise of a planetary citizenship.